Retinoic acid synthesis and autoregulation mediate zonal patterning of vestibular organs and inner ear morphogenesis - Ono, Kazuya (Development, 2020)
Retinoic acid (RA), a vitamin A (retinol) derivative, has pleiotropic functions during embryonic development. The synthesis of RA requires two enzymatic reactions: oxidation of retinol into retinaldehyde by alcohol dehydrogenases (ADHs) or retinol dehydrogenases (RDHs); and oxidation of retinaldehyde into RA by aldehyde dehydrogenases family 1, subfamily A (ALDH1as), such as ALDH1a1, ALDH1a2 and ALDH1a3. Levels of RA in tissues are regulated by spatiotemporal expression patterns of genes encoding RA-synthesizing and -degrading enzymes, such as cytochrome P450 26 (Cyp26 genes). Here, we show that RDH10 is important for both sensory and non-sensory formation of the vestibule of the inner ear. Mice deficient in Rdh10 exhibit failure of utricle-saccule separation, otoconial formation and zonal patterning of vestibular sensory organs. These phenotypes are similar to those of Aldh1a3 knockouts, and the sensory phenotype is complementary to that of Cyp26b1 knockouts. Together, these results demonstrate that RDH10 and ALDH1a3 are the key RA-synthesis enzymes involved in vestibular development. Furthermore, we discovered that RA induces Cyp26b1 expression in the developing vestibular sensory organs, which generates the differential RA signaling required for zonal patterning.